Comparison of Ticagrelor and Clopidogrel in Elective Coronary Stenting: A Double Blind Randomized Clinical Trial - Mohammadjavad Mehdizadeh Parizi; Reza Golchin Vafa; Amin Ahmadi; Reza Heydarzade; Mehrdad Sadeghi; Amin Khademolhossseini; Farhang Amiri; Soroush Khoshnood Mansorkhani; Ali Tavan; Nazanin Hosseini; Mohammad Montaseri; Seyed Ali Hosseini; et al. (Journal of Interventional Cardiology)
Background. Dual antiplatelet therapy with a P2Y12 inhibitor (e.g., clopidogrel and ticagrelor) and aspirin is recommended for at least one year after percutaneous coronary intervention (PCI) to prevent further myocardial infarction and stent thrombosis as the major adverse effects of PCI. Methods. This randomized clinical trial was conducted from October 2022 to March 2023. Patients who had undergone elective PCI were included in the study. Patients were randomized into two different groups. One group took ASA 80 mg and clopidogrel 75 mg once daily, while the other took ASA 80 mg once daily and ticagrelor 90 mg twice daily. After six months of close follow-up, patients were asked to score their dyspnea on a 10-point Likert scale. They were also asked about dyspnea on exertion, paroxysmal nocturnal dyspnea (PND), bleeding, and the occurrence of major adverse cardiovascular events (MACEs). Results. 223 patients were allocated to the clopidogrel group and 214 to the ticagrelor group. In the ticagrelor group, 95 patients (44.3%) reported dyspnea at rest, compared with only 44 patients (19.7%) in the clopidogrel group (P < 0.001). MACEs occurred in 7 patients (2.8%) in the ticagrelor group, compared with 16 (7.6%) in the clopidogrel group (P = 0.031). Eight patients (3.8%) reported bleeding with ticagrelor, as did seven (3.2%) with clopidogrel (P = 0.799). Conclusions. New-onset dyspnea was recorded more frequently with ticagrelor than clopidogrel, yet fewer MACEs occurred with ticagrelor (ClinicalTrials.gov number: NCT05858918).